Bioproduct Potential of Outdoor Cultures of Tolypothrix sp.: Effect of Carbon Dioxide and Metal-Rich Wastewater - Velu, Chinnathambi; Cirés, Samuel; Brinkman, Diane L.; Heimann, Kirsten (Frontiers in Bioengineering and Biotechnology, 2020)
Rising CO2 levels, associated climatic instability, freshwater scarcity and diminishing arable land exacerbate the challenge to maintain food security for the fast growing human population. Although coal-fired power plants generate large amounts of CO2 emissions and wastewater, containing environmentally unsafe concentrations of metals, they ensure energy security. Nitrogen (N2)-fixation by cyanobacteria eliminate nitrogen fertilization costs, making them promising candidates for remediation of waste CO2 and metals from macronutrient-poor ash dam water and the biomass is suitable for phycocyanin and biofertilizer product development. Here, the effects of CO2 and metal mixtures on growth, bioproduct and metal removal potential were investigated for the self-flocculating, N2-fixing freshwater cyanobacterium Tolypothrix sp. Tolypothrix sp. was grown outdoors in simulated ash dam wastewater (SADW) in 500 L vertical bag suspension cultures and as biofilms in modified algal-turf scrubbers. The cultivation systems were aerated with air containing either 15% CO2 (v/v) or not. CO2-fertilization resulted in ∼1.25- and 1.45-fold higher biomass productivities and ∼40 and 27% increased phycocyanin and phycoerythrin contents for biofilm and suspension cultures, respectively. CO2 had no effect on removal of Al, As, Cu, Fe, Sr, and Zn, while Mo removal increased by 37% in both systems. In contrast, Ni removal was reduced in biofilm systems, while Se removal increased by 73% in suspension cultures. Based on biomass yields and biochemical data obtained, net present value (NPV) and sensitivities analyses used four bioproduct scenarios: (1) phycocyanin sole product, (2) biofertilizer sole product, (3) 50% phycocyanin and 50% biofertilizer, and (4) 100% phycocyanin and 100% biofertilizer (residual biomass) for power station co-located and not co-located 10 ha facilities over a 20-year period. Economic feasibility for the production of food-grade phycocyanin either as a sole product or with co-production of biofertilizer was demonstrated for CO2-enriched vertical and raceway suspension cultures raised without nitrogen-fertilization and co-location with power stations significantly increased profit margins.